The Value of a High School GPA - Landaud, Fanny; Maurin, Éric; Willage, Barton; Willén, Alexander (The Review of Economics and Statistics, 2026)
Abstract This paper provides novel evidence on the causal effect of high school Grade Point Average (GPA) on the human capital development and labor market trajectory of individuals. Causal identification is achieved by exploiting a unique feature of the Norwegian education system that produces exogenous variation in GPA among high school students. We find little effect on the number of completed years of higher education, but significant effects on the number and quality of higher education programs available to students after high school. Most importantly, we find persistent effects on students’ long-run labor market outcomes, most notably market wage.